Wordwall-Based Gamification to Improve Understanding of the Demand Function: A Madrasah Aliyah Case Study - Kadir, Siti Khadijah Abdul; Ndori, Vinsesnsius Herianto; Bajo, Firmina Dinenti; Ayusari, Ayusari (Actual Insight, 2025)
Understanding the concept of the demand function in economic mathematics is still a challenge for Madrasah Aliyah students due to the abstract and applicative nature of the material. This study aims to analyze the effectiveness of gamification using the Wordwall platform in improving students’ understanding of the demand function concept at MAS At-Taqwa Beru. This study uses a qualitative approach with a case study design involving 30 eleventh-grade students selected through purposive sampling. Data were collected through participatory observation, semi-structured interviews, and documentation, and analyzed thematically. The results showed an increase in active student participation from 55% to 80% during gamification learning and an increase in the average learning score from 62.3 to 78.5 (gain ±26%). Wordwall facilitated students’ understanding through interactive visualization and contextual questions, stimulated intrinsic motivation, and encouraged collaboration among students. These findings support social constructivism theory and Self-Determination Theory that interaction, autonomy, and instant feedback are important in building conceptual understanding. Theoretically, this research enriches the literature on gamification in economics learning at the Madrasah level, while practically recommending the integration of Wordwall as an effective alternative learning medium, supported by digital facilities and school policies so that its implementation can be carried out systematically and sustainably.